Some Characterizations of Riesz- Valued Sequence Spaces Generated by an Order ϕ-Function. (2nd January 2018) - Herawati, E.; Supama,; Mursaleen, M.; Nasution, M.
ABSTRACT: In this paper, we introduce an order ϕ -function on a Riesz space. Further, we construct a Riesz- Valued Sequence spaces using the ϕ -function and obtain the condition to characterize these spaces.